Critical Limb Ischemia: A Practical Up-To-Date Review. (July 2018) - Fabiani, Iacopo; Calogero, Enrico; Pugliese, Nicola Riccardo; Di Stefano, Rossella; Nicastro, Irene; Buttitta, Flavio; Nuti, Marco; Violo, Caterina; Giannini, Danilo; Morgantini, Alessandro; Conte, Lorenzo; Barletta, Valentina; et al.
Critical limb ischemia (CLI) is the most advanced form of peripheral artery disease. It is associated with significant morbidity and mortality and high management costs. It carries a high risk of amputation and local infection. Moreover, cardiovascular complications remain a major concern. Although it is a well-known entity and new technological and therapeutic advances have been made, this condition remains poorly addressed, with significantly heterogeneous management, especially in nonexperienced centers. This review, from a third-level dedicated inpatient and outpatient cardioangiology structure, aims to provide an updated summary on the topic of CLI of its complexity, encompassing epidemiological, social, economical and, in particular, diagnostic/imaging issues, together with potential therapeutic strategies (medical, endovascular, and surgical), including the evaluation of cardiovascular risk factors, the diagnosis, and treatment together with prognostic stratification.